A representação da ditadura na literatura: memória e ficção em O Fantasma de Luís Buñuel E K. – Relato de uma Busca - Araujo, Amanda Arruda Venci (2015)
The following work aims to analyze the representation that the Military Coup of 1964 – and the dictatorial period that followed it – had in Brazilian Literature of the beginning of the 21st century, based on the novels O Fantasma de Luis Buñuel (2004), by Maria José Silveira and K. – Relato de uma Busca (2014), by Bernardo Kucinski. In order to do so, Le Goff (2013), Pollak (1989; 1992) and Ricoeur are important sources that help us to better understand the theoretical basis concerning memory, while Lima (2006), Reuter (2004), Martins (2011) and Lejeune (1996) are the theoretical basis on the study of fiction, autofiction and autobiography. Thus, there are subsidies to verify the relationship between reality and memory of the period and the fiction produced from it.